Identification and Classification of Desirable Web-Based Services from the Perspective of Website Users of Iran's Hospitals Based on Kano Model of Customer Satisfaction - Zahra Mohammadzadeh; Hamid Reza Saeidnia; Ali Ghorbi (Tehran University of Medical Sciences, 2020)
Background and Aim: A hospital website is an appropriate system for exchanging information and connecting patients, hospitals and medical staff. The purpose of this study was to identify and classify desirable web-based services in websites of Iranchr('39')s hospitals based on Kano's Customer Satisfaction Model. Materials and Methods: This was a survey study. The statistical population of the study consisted of hospital website users, of whom 120 were randomly selected. The data collection tool was a questionnaire based on Kano model. The validity of the questionnaire was confirmed by the information science and health information technology(HIT) professors. Data were analyzed using Kano model evaluation table, Excel software, and descriptive statistics. Cronbachchr('39')s alpha test was used to determine reliability(a=0.82). Results: First, the desirable web-based services of the hospitals' websites were identified. Then, 67 identified services were classified into mandatory criteria(29 services), one-dimensional criteria(15 services), attractive criteria(14 services) and indifferent criteria(9 services). Most services were mandatory, attractive, one-dimensional and indifferent in content components. Conclusion: Most services identified in this study were on the websites of the worldchr('39')s leading hospitals; HIT designers and professionals and hospital managers are expected to use such services in designing hospital websites. Although the comments of site designers and experts were practical in some cases, they attracted a limited number of users due to their unfamiliarity with specialized website design topics.